Personnel Motivation to Share Knowledge for Quality Assurance: the role of Intrinsic and Extrinsic Motivation - Devi Rahnjen Wijayadne; William Widjaja (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Quality assurance has become the most critical behavior to expand business across the country. To assure the quality of the product, every employee should understand the knowledge about the standard operating procedure and quality assessment requirement, so the enterprise should manage and share knowledge with each employee in the organization. The best way to manage and share knowledge is knowledge sharing among employees, defined as knowledge sharing behavior. This research examines the role of extrinsic motivation dan intrinsic motivation to enhance employee’s knowledge sharing behavior (KSB). This empirical study aims to confirm and examine these types of motivation that influence KSB. Self-determined theory (SDT) and social exchange theory (SCT) are used to understand the role of motivation and organizational context that influence employee KSB. Research models are analyzed using structural equation modeling partial least square (SEM-PLS). The result is finding a positive effect of extrinsic and intrinsic motivation to determine employees (KSB) who support SDT and SCT.